2018
DOI: 10.1192/bja.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Depression and obesity: can the cycle be broken?

Abstract: SUMMARYObesity and depression are conditions that have been linked through a great number of interesting mechanisms. To fully understand the implications of treatment choices it is necessary to continue to investigate the physiology of these two conditions. By examining the background of these problems and considering factors such as stress response, neurological change and systemic inflammation, we propose a cycle linking depression and obesity. With reference to this cycle, we discuss management options, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(57 reference statements)
0
6
1
1
Order By: Relevance
“…Such increase in global energy consumption and in foods rich in fat and sugar promotes weight gain. Although this study found no correlation between the symptoms of depression, adiposity, or abdominal perimeter, analyses of longitudinal studies comparing a bidirectional association between obesity and depression are common in the scientific literature, especially among women [36,54].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Such increase in global energy consumption and in foods rich in fat and sugar promotes weight gain. Although this study found no correlation between the symptoms of depression, adiposity, or abdominal perimeter, analyses of longitudinal studies comparing a bidirectional association between obesity and depression are common in the scientific literature, especially among women [36,54].…”
Section: Discussioncontrasting
confidence: 73%
“…Most obese individuals have high serum levels of leptin that are compatible with their adipose mass, suggesting that the mechanism is more a resistance to the action of this hormone than to the lack of it [33][34][35]. This state of hyperleptinemia produces an inadequate response in weight loss therapy and favors the inflammatory process in the constellation of chronic diseases [36]. In this study, it was shown that interdisciplinary therapy promoted a significant reduction in body mass (Δ -5.36 p < 0.001) (▶Supplementary Table 1S) and consequently in serum levels of leptin (Δ -15.62 ng/ml p < 0.001) and in leptin/adiponectin ratio (Δ -0.84 p < 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing severity of depression is also associated with greater all-cause mortality including cardiovascular event and stroke [5]. Although there are many causes of depression, there is a well-established link between obesity and depression synergistically decreasing both physical and mental quality of life [6] as affected individuals enter a vicious cycle; worsening depression is associated with weight gain which, in turn, leads to worse depression outcomes [7]. As a directly proportional relationship between risk of depression and obesity becomes established in the literature [8], the need for a treatment that can address both conditions is increasingly clear.…”
Section: Introductionmentioning
confidence: 99%
“…Obesitas dan depresi merupakan kondisi umum yang memiliki efek individu yang signifikan. Secara bersama-sama, telah ditunjukkan bahwa depresi dan obesitas berdampak negatif pada kualitas hidup secara sinergis (Romain et al, 2018). Hubungan dua arah telah banyak dinilai saling berkesinambungan tetapi tidak semua studi mendukung hal ini, menunjukkan bahwa hubungan tersebut bersifat kompleks (Singh et al, 2014).…”
Section: Hasil Dan Pembahasanunclassified